Solar UAV : design, fabrication and testing of a test wing section and integration with solar cells - Pang, Yida. (2012)
Unmanned Aerial Vehicles (UAV) have seen an unprecedented growth in recent years in both the military and the civilian applications domains. As such, this has led to heightened interest and research activities in unmanned technology at the academic level. This report shows the conceptual design of a solar powered UAV that has a wingspan of 15m with a takeoff mass of not more than 60kg. The conceptual idea is adopted from a powered glider that is designed to have minimum drag for any given amount of lift. Minimum drag is achieved through a long and narrow fuselage section and long and thin wings. With such an aircraft design, the aircraft is able to have efficient climbing rates and can glide long distances at a high speed with a minimum loss of height in between. The idea is to use minimal energy to propel the solar UAV to stay airborne.